2005
DOI: 10.1242/dev.01925
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic epithelial plasticity mediated by acinar cell transdifferentiation and generation of nestin-positive intermediates

Abstract: Epithelial metaplasia occurs when one predominant cell type in a tissue is replaced by another, and is frequently associated with an increased risk of subsequent neoplasia. In both mouse and human pancreas, acinar-to-ductal metaplasia has been implicated in the generation of cancer precursors. We show that pancreatic epithelial explants undergo spontaneous acinar-to-ductal metaplasia in response to EGFR signaling, and that this change in epithelial character is associated with the appearance of nestin-positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
308
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 314 publications
(340 citation statements)
references
References 37 publications
20
308
3
1
Order By: Relevance
“…For example, diverting just a few percent away for conversion to b-cells might not compromise overall organ function. Several in vitro acinar cell culture studies demonstrated a potential acinar to endocrine/duct conversion when treated with EGF, nicotinamide, or TGF-a (for example, Means et al, 2005;Minami et al, 2005). Upon caerulein treatment in vivo, acinar cells transiently dedifferentiate to a progenitor-like state, based on the observation of Pdx1, Foxa2, Sox9, and Hes1 positivity (Jensen et al, 2005).…”
Section: Injury-induced Reprogrammingmentioning
confidence: 99%
“…For example, diverting just a few percent away for conversion to b-cells might not compromise overall organ function. Several in vitro acinar cell culture studies demonstrated a potential acinar to endocrine/duct conversion when treated with EGF, nicotinamide, or TGF-a (for example, Means et al, 2005;Minami et al, 2005). Upon caerulein treatment in vivo, acinar cells transiently dedifferentiate to a progenitor-like state, based on the observation of Pdx1, Foxa2, Sox9, and Hes1 positivity (Jensen et al, 2005).…”
Section: Injury-induced Reprogrammingmentioning
confidence: 99%
“…La partie exocrine du pancréas, composée principalement des cellules acinaires, est très majoritaire et pourrait ainsi représenter une source attractive de précurseurs que l'on pourrait « convertir » en cellules endocrines. De récentes études ont en effet démontré la plasticité de ces cellules in vitro et in vivo, et leur capacité de transdifférenciation vers un destin endocrine [16][17][18]. Ainsi, les travaux de Zhou et al [19] suggèrent la possibilité d'une reprogrammation des cellules acinaires différenciées.…”
Section: Plasticité Des Cellules Acinairesunclassified
“…Upon stress, acinar cells readily undergo a phenotypic switch resulting in loss of differentiation and acquisition of duct-like features both in vivo and in vitro (2)(3)(4)(5)(6). Together with their minimal proliferative potential, these effects hamper the study of acinar differentiation.…”
Section: Introductionmentioning
confidence: 99%